Artemis 123: development of a whole-head infant and young child MEG system - Roberts, Timothy P.; Paulson, Douglas N.; Hirschkoff, Gene; Pratt, Kevin; Mascarenas, Anthony; Miller, Paul; Han, Mengali; Caffrey, Jasom; Kincade, Chuck; Power, William; Murray, Rebecca E.; Chow, Vivian; et al. (Frontiers in Human Neuroscience, 2014)
Background: A major motivation in designing the new infant and child magnetoencephalography (MEG) system described in this manuscript is the premise that electrophysiological signatures (resting activity and evoked responses) may serve as biomarkers of neurodevelopmental disorders, with neuronal abnormalities in conditions such as autism spectrum disorder potentially detectable early in development. Whole-head MEG systems are generally optimized/sized for adults. Since magnetic field produced by neuronal currents decreases as a function of distance^2 and infants and young children have smaller head sizes, whole-head adult MEG systems do not provide optimal signal-to-noise in younger individuals. This spurred development of a whole-head infant and young child MEG system – Artemis 123. Methods: In addition to describing the instrument design, the focus of this manuscript is use of Artemis 123 to obtain auditory evoked and resting-state neuromagnetic data in young children. Data were collected from a 14-month female, an 18-month female, and a 48-month male. Phantom data are also provided to show localization accuracy. Results: Artemis 123 auditory data showed generalizability and reproducibility, with auditory responses observed in all participants. The auditory MEG measures were found to be manipulable, exhibiting sensitivity to tone frequency. Furthermore, there appeared to be a predictable sensitivity of evoked components to development, with latencies decreasing with age. Resting-state showed characteristic oscillatory activity. Finally, phantom data showed that dipole sources could be localized with an error< 0.5cm. Conclusions: Artemis 123 allows efficient recording of whole-head MEG in infants four years and younger. Future work will examine the feasibility of obtaining somatosensory and visual recordings in similar-age children as well as obtaining recordings from younger infants. Thus, Artemis 123 offers the promise of detecting earlier diagnostic signatures